Archiving of mutations in HIV‐1 cellular reservoirs among vertically infected adolescents is contingent with clinical stages and plasma viral load: Evidence from the EDCTP‐READY study. Issue 6 (23rd December 2021) - Fokam, Joseph; Mpouel Bala, Marie Laure; Santoro, Maria‐Mercedes; Takou, Désiré; Tala, Valère; Beloumou, Grace; Ngoufack, Ezechiel Semengue; Chenwi, Collins; Pabo Willy Leroi, Togna; Njume, Debimeh; Teto, Georges; Dambaya, Beatrice; et al.
Abstract: Introduction: Globally, HIV‐related adolescent deaths have increased about 50%, especially for those who are vertically infected. This could be driven by archived drug resistance mutations (DRMs) as children grow up, which might jeopardize antiretroviral therapy (ART). Our objective was to compare HIV‐1 genotypic variation between plasma RNA and proviral DNA of vertically infected adolescents (aged 10–19 years) failing ART. Methods: A comparative study was conducted in 2019 among 296 adolescents with perinatal HIV infection (ALPHI) failing ART in health facilities of the Centre Region of Cameroon. The WHO clinical stage, CD4 count and plasma viral load (PVL) were measured. For those failing ART (PVL ≥ 1000 copies/mL), RNA (plasma) and proviral DNA (buffy coat) were sequenced in the pol gene at Chantal BIYA International Reference Centre (CIRCB), Yaoundé, Cameroon. HIV‐1 subtypes and DRMs were interpreted using Stanford HIVdb v.8.8 and MEGA‐X. Results: Of the 30% (89/296) failing ART, 81 had both RNA and DNA sequences generated and three were excluded for APOBEC mutations: the mean age was 16 ± 3 years; female‐to‐male ratio was 3:5; median PVL was 46 856 copies/mL [interquartile range (IQR): 19 898–271 410]; median CD4 count was 264 cells/μL (IQR: 131–574); and 42% were at WHO clinical stage 3/4. Subtype concordance between RNA and DNA viral strains was 100%, with CRF02_AG being predominant (65%) and two potential new recombinants found (A1/G/K; F1/G). Adolescents with DRMs were significantly higher in plasma than in proviral DNA (92% vs. 86%, p  < 0.0001). Prevalent DRMs by drug class (RNA vs. DNA respectively) were at position M184 (74% vs. 67%) for nucleoside reverse transcriptase inhibitors (NRTIs), K103 (63% vs. 59%) for non‐NRTIs, and V82, L76 and M46 (2% vs. 2%) for protease inhibitors. A total of 35% (27/78) of adolescents had concordant DRM profiles in RNA and DNA, while 27% (21/78) had DRMs only in proviral DNA. The presence of archived DRMs was associated with advanced clinical stage 3/4 (OR = 0.14, p  = 0.0003) and PVL < 5 Log (Copies/mL) (OR: 4.88, p  = 0.006). Conclusions: Although plasma RNA remains more sensitive for detecting HIV‐1 DRMs, about a quarter of ALPHI experiencing ART failure in an African setting might have archived DRMs in viral reservoirs, indicating clinically occult resistance. Thus, to ensure effective ART success, proviral DNA profiling (alongside RNA genotyping) would provide additional DRMs for adolescents with advanced clinical stages and/or moderate PVL.